Estimativa da infiltração e do afluxo devidos à precipitação na rede de esgoto sanitário em município de pequeno porte - Festi, Aparecido Vanderlei (Universidade Federal de São Carlos, 2006)
The main purpose of this work was to identify and to estimate the rainfall derived infiltration and inflow (IADP) into the sewer in a small city and to do an analysis of their influence on this collection system. This work was composed by field measurements on the sewage flowrate output and volume arriving to the Sewage Pumping Plant Station, simultaneously to the collection and measurement of rainfall on the corresponding same urban watershed area of the Borborema, in São Paulo State. The existing methodologies were divided in the follow steps: choosing and characterization of the working field; data collection of the sewage volume and flowrate; collection of the rainfall data; choosing and characterization of the data collected; employment of existing models and methodologies useful to the present available data, in order to derive the underground water infiltration rate and the overflow occurring in the sewage colletion network. The volumetric and percentile IADP were quantified. The constant unitary rate (TUC) was also estimated, by several ways. The results allowed obtaining mathematical formulations to derive the IADP and TUC of the Borborema s sewage network. Such mathematical formulations are suitable to be applied in urban areas of cities of a similar to that of Borborema. It was estimated that the IADP can generate flowrates 2,5 times greater than the sewage flows in dry weather and infiltration rates in the sewage network similar to those adopted for system design. The work allowed to estimate how complex are the infiltration and inflow of stormwater in the sewer network. The methodologies applied were quite simple and may be easily applied in other cities.
Keywords: Esgoto sanitário; Drenagem urbana; Sobrecarga; Taxa de infiltração; Infiltration and inflow due to rainfall; Infiltration rate; Sewer network; Sanitary sewer overflow; Urban drainage; Sewage measurement; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO BASICO::DRENAGEM DE AGUAS RESIDUARIAS